2021
DOI: 10.3390/ani11010206
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Antimicrobial Resistance and Molecular Detection of mcr-1 Gene in Salmonella Species Isolated from Chicken

Abstract: Colistin (polymyxin E) is widely used in animal and human medicine and is increasingly used as one of the last-resort antibiotics against Gram-negative bacilli. Due to the increased use of colistin in treating infections caused by multidrug-resistant Gram-negative bacteria, resistance to this antibiotic ought to be monitored. The study was undertaken to elucidate the molecular mechanisms, genetic relationships and phenotype correlations of colistin-resistant isolates. Here, we report the detection of the mcr-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
0
10
1
2
Order By: Relevance
“…In this review, we found that 17.19%, 28.57% and 30% of salmonellae were present in water, transport swab and air samples from poultry farm environments in Bangladesh [25,33,39,41]. This study also observed that average 26.30% of the cloacal swab samples, 42% of the visceral organ samples and 60% of intestinal fluid samples were infected with Salmonella [24,32,38,44,45,48]. Salmonella infection in poultry farm samples has been documented from many regions of the world, with rates of 17%, 35%, 36%, 39% and 53% in the United States, Spain, Korea, Brazil and Vietnam, respectively [71,72].…”
Section: Overall Prevalence Of Salmonellamentioning
confidence: 83%
See 1 more Smart Citation
“…In this review, we found that 17.19%, 28.57% and 30% of salmonellae were present in water, transport swab and air samples from poultry farm environments in Bangladesh [25,33,39,41]. This study also observed that average 26.30% of the cloacal swab samples, 42% of the visceral organ samples and 60% of intestinal fluid samples were infected with Salmonella [24,32,38,44,45,48]. Salmonella infection in poultry farm samples has been documented from many regions of the world, with rates of 17%, 35%, 36%, 39% and 53% in the United States, Spain, Korea, Brazil and Vietnam, respectively [71,72].…”
Section: Overall Prevalence Of Salmonellamentioning
confidence: 83%
“…Ciprofloxacin, a sort of fluoroquinolone antimicrobials, is commonly used to treat a vast extend infections of humans, poultry, and other animals. As a result, Salmonella isolated from broilers, layers and turkeys showed periodical increase in resistance to ciprofloxacin, ranging from 20% to 100% [24,28,30,37,42,44,47] in different districts of Bangladesh in between 2012 to 2021. The scenario is similar in neighboring countries.…”
Section: Resistance To Fluroquinolonesmentioning
confidence: 99%
“…Similar findings (46.87%) were reported by earlier researchers in India [ 43 ]. But higher resistance against colistin (92.68%) was recorded in Bangladesh [ 47 ] and lesser (20%) in Serbia [ 48 ] and (4.76%) in Mumbai, India [ 49 ]. It is beyond the scope of this study to attribute colistin resistance to a particular reason.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, colistin has been used in livestock and poultry for decades all over the world [ 14 ]. The emergence of colistin resistance was previously reported [ 15 , 16 , 17 ]. As a result, it’s not surprising that widespread use of colistin in food-producing animals has aided the spread of colistin resistance [ 14 ].…”
Section: Introductionmentioning
confidence: 89%
“…MCR-1 proteins’ transmembrane helices were predicted using the TMHMM server ( accessed on 16 March 2021) and standard parameters, as reported recently [ 17 ]. When the loop was on the inside or outside, the topology was given as the location of the transmembrane helices differentiated by I and ‘o’ [ 38 ].…”
Section: Methodsmentioning
confidence: 99%